2021
DOI: 10.1101/2021.12.21.473706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 human antibodies retaining neutralizing activity against SARS-CoV-2 B.1.1.529 (omicron)

Abstract: SARS-CoV-2 B.1.1.529, designated omicron, was recently identified as a new variant of concern by WHO and is rapidly replacing SARS-CoV-2 delta as the most dominant variant in many countries. Unfortunately, because of the high number of mutations present in the spike of SARS-CoV-2 omicron, most monoclonal antibodies (mAbs) currently approved for treatment of COVID-19 lose their in vitro neutralizing activity against this variant. We recently described a panel of human anti-SARS-CoV-2 mAbs that potently neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These sensitivities need to be reassessed as new variants emerge. According to the National Institutes of Health (NIH), rapid antigen tests continue to detect cases of the Omicron variant, although “reduced sensitivity” has been noted in early laboratory studies with some brands [ 66 , 67 ].…”
Section: Immunological Assays: Antigen and Antibody-based Techniquesmentioning
confidence: 99%
“…These sensitivities need to be reassessed as new variants emerge. According to the National Institutes of Health (NIH), rapid antigen tests continue to detect cases of the Omicron variant, although “reduced sensitivity” has been noted in early laboratory studies with some brands [ 66 , 67 ].…”
Section: Immunological Assays: Antigen and Antibody-based Techniquesmentioning
confidence: 99%
“… 74 Omicron was observed to escape neutralization with a cocktail of imdevimab, and casirivimab 64 or the all the other tested Mabs (casirivimab, imdevimab, bamlanivimab, cilgavimab, and tixagevimab), 26 and only sotrovimab was observed to neutralize the virus. 26 , 64 In a study by Imbrechts et al, 97 after testing various mAbs against all the five VOCs of SARS‐Cov‐2, however, it was concluded that three mAbs including mAb 3B8 at very low doses resulted in complete neutralization of Omicron variant. Identification of more such mAbs can give confidence to handle the continuously evolving novel variants in SARS‐CoV‐2.…”
Section: Efficacy Of Antibody Based Therapeutics Used For Sars‐cov‐2 ...mentioning
confidence: 99%